Compliance and persistence with daily, weekly, and monthly bisphosphonates for osteoporosis in Japan: analysis of data from the CISA. Issue 1 (December 2015) - Kishimoto, Hideaki; Maehara, Masayuki
Abstract Summary Compliance and persistence with daily, weekly, and monthly bisphosphonates (BPs) for osteoporosis were assessed using data from the Platform for Clinical Information Statistical Analysis (CISA) database that contains data of prescriptions in 13 university hospitals in Japan. The analysis revealed compliance and persistence improved as the dosing interval increases. Purpose BPs are an effective first-line therapy for osteoporosis, but adherence is low. Compliance (medication possession ratio, MPR) and persistence (time to discontinuation) with daily, weekly, and monthly BPs were compared to ensure better adherence. Methods Using data from the CISA database containing prescription data in 13 university hospitals in Japan, adherence to oral BPs of osteoporotic patients was investigated. Daily and weekly BPs were compared for compliance and persistence over 5 and 8 years, and daily, weekly, and monthly BPs for those over 1 and 2 years. Results MPR over 5 years was 20.8 and 60.9 % for daily and weekly BPs (p  < 0.001), respectively. MPR over 1 year was 38.6, 70.6, and 77.7 % for daily, weekly, and monthly BPs (P  < 0.001), respectively. Persistence over 8 years was significantly higher in weekly than daily BPs (p  < 0.001), and that over 5 years was highest in patients receiving BPs monthly (p  < 0.01). Conclusion The present analysis indicates that a monthly regimen has better adherence to treatment as compared with weekly and daily regimens.